2018
DOI: 10.1002/anie.201806140
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Uranium‐based Endohedral Metallofullerenes (EMFs) by Selective Supramolecular Encapsulation and Release

Abstract: Supramolecular nanocapsule 1⋅(BArF) is able to sequentially and selectively entrap recently discovered U @C and unprecedented Sc CU@C , simply by soaking crystals of 1⋅(BArF) in a toluene solution of arc-produced soot. These species, selectively and stepwise absorbed by 1⋅(BArF) , are easily released, obtaining highly pure fractions of U @C and Sc CU@C in one step. Sc CU@C represents the first example of a mixed metal actinide-based endohedral metallofullerene (EMF). Remarkably, the host-guest studies revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 28 publications
1
45
0
Order By: Relevance
“…demonstrated that EMFs with specific cage structures or internal cluster species can be selectively purified by encapsulation of EMFs into supramolecular nanocapsules . Following this strategy, a series of EMFs, i.e., Sc 3 N@C 80 , U 2 @C 78,80 , U 2 C@C 78,80 , and Sc 2 CU@C 80 were successfully obtained from different crude soot. From the aforementioned discussion, the non‐chromatographic methods for the purification of EMFs have proven to be efficient strategies in addition to HPLC methods, and have led to more EMFs with new cage structures and internal clusters being separated and purified.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that EMFs with specific cage structures or internal cluster species can be selectively purified by encapsulation of EMFs into supramolecular nanocapsules . Following this strategy, a series of EMFs, i.e., Sc 3 N@C 80 , U 2 @C 78,80 , U 2 C@C 78,80 , and Sc 2 CU@C 80 were successfully obtained from different crude soot. From the aforementioned discussion, the non‐chromatographic methods for the purification of EMFs have proven to be efficient strategies in addition to HPLC methods, and have led to more EMFs with new cage structures and internal clusters being separated and purified.…”
Section: Introductionmentioning
confidence: 99%
“…They also successfully synthesized and characterized the long‐dreamed U 2 @I h (7)‐C 80 , which features a weak U–U metal bond . Very recently, the first mixed metal actinide‐based EMF Sc 2 CU@I h (7)‐C 80 and the novel uranium carbide UCU@I h (7)‐C 80 were continually prepared and successfully characterized . Despite these fascinating contributions, however, the structures and properties of actinide EMFs still remain largely undisclosed.…”
Section: Introductionmentioning
confidence: 99%
“…[29] Very recently, the first mixed metal actinide-based EMF Sc 2 CU@I h (7)-C 80 and the novel uranium carbide UCU@I h (7)-C 80 were continually prepared and successfully characterized. [30,31] Despite these fascinating contributions, however, the structures and properties of actinide EMFs still remain largely undisclosed. Moreover, to our knowledge, there is no report focused on the relationship between any actinide metal and the distribution of cage pentagons thus far, although, as mentioned above, the latter largely determines the EMF stability and dominates the metal-cage electronic interactions.…”
mentioning
confidence: 99%
“…Expanding the scope of coordination-driven self-assembly strategies, several researchers have recently discovered that cis-capped Pt(II) and Pd(II) corners can simultaneously bind a carboxylate and a pyridyl ligands, preferentially yielding thermodynamically favored heteroleptic Pt(N,O) complexes instead of two different homoleptic complexes. [29][30][31][32][33][34][47][48][49][50][51][52][53] Furthermore, when two different homoleptic Pt II (COO -)2 and Pt II (pyridyl)2 complexes were mixed together at an appropriate stoichiometry, they spontaneously reorganized into thermodynamically more stable heteroleptic Pt(N,O) complexes. 30,32,33 These revelations paved the door for metal-driven self-assembly of tricomponent metallacycles and cages containing two complementary ligands that could further diversify their structures, compositions, properties, and functions.…”
Section: Introductionmentioning
confidence: 99%